Mass Spectrometric Fingerprint Mapping Reveals Species-Specific Differences in Plant Polyphenols and Related Bioactivities - Vanhakylä Suvi; Salminen Juha-Pekka (MDPI, 2025)
Plant species show large variation in the composition and content of their tannins and other polyphenols. These large metabolites are not easy to measure accurately, but they are important factors for species bioactivity and chemotaxonomy. Here, we used an automated group-specific UHPLC-DAD-MS/MS tool to detect and quantify eight most common polyphenol groups in 31 chemically diverse plant species representing many types of growth forms and evolutionary ages. Ten replicate plants were used for each species and two polyphenol-related bioactivities, i.e., protein precipitation capacity and oxidative activity were measured in all samples as well. By the help of a novel 2D fingerprint mapping tool we were able to visualize the qualitative and quantitative differences between the species in hydrolysable tannins (galloyl and hexahydroxydiphenoyl derivatives), proanthocyanidins (procyanidins and prodelphinidins), flavonols (kaempferol, quercetin and myricetin derivatives) and quinic acid derivatives together with the two bioactivities. The highest oxidative activities were found with species containing ellagitannins (e.g., Quercus robur, Geranium sylvaticum, Lythrum salicaria and Chamaenerion angustifolium) or prodelphinidin-rich proanthocyanidins (e.g., Ribes alpinum, Salix phylicifolia and Lysimachia vulgaris). The best species with high protein precipitation capacity were rich in gallotannins (Acer platanoides and Paeonia lactiflora) or oligomeric ellagitannins (e.g., Comarum palustre, Lythrum salicaria and Chamaenerion angustifolium). These types of tools could prove their use in many types of screening experiments and might reveal even unusually active polyphenol types directly from the crude plant extracts.